Tunable, biodegradable grafting-from glycopolypeptide bottlebrush polymers - Zachary S. Clauss (Nature Portfolio, 2021)
Synthetic mimics of glycoproteins and proteoglycans have wide applications in biomedicine, yet preparation has been challenged by their high grafting and glycosylation densities. Here the authors show one-pot dual-catalysis polymerization of glycan-bearing α-amino acid N-carboxyanhydrides to form glycopolypeptide brushes.